Genetic diversity and relationships among native Dendrobium species from Bali, Indonesia, using SSR markers - IDA AYU PUTRI DARMAWATI; RINDANG DWIYANI; NI LUH MADE PRADNYAWATHI; YUYUN FITRIANI; LISTIHANI LISTIHANI; RINI HERMINA KAMUHI (Asian Journal of Agriculture, 2025)
Abstract. Darmawati IAP, Dwiyani R, Pradnyawathi NLM, Fitriani Y, Listihani L, Kamuhi RH. 2025. Genetic diversity and relationships among native Dendrobium species from Bali, Indonesia, using SSR markers. Asian J Agric 9: 917-924. Bali, Indonesia, has significant potential for the development of orchid cultivation, particularly through the production of hybrids that meet market preferences. Among various orchid genera, Dendrobium holds major economic and horticultural importance due to its wide adaptability, aesthetic value, and high demand in both domestic and international markets. Wild Dendrobium species represent an invaluable source of germplasm that can be used for interspecific hybridization and the development of new cultivars with desirable characteristics such as flower color, shape, and durability. However, the lack of information on the genetic diversity of native Dendrobium species in Bali limits their effective use in breeding and conservation programs. This study aimed to evaluate the genetic diversity and relationships among 24 native Dendrobium species collected from 12 forest areas across Bali using Simple Sequence Repeat (SSR) markers. The molecular analysis revealed high genetic variation, with 86.21 percent of loci showing polymorphism and moderate heterozygosity across populations. Genetic similarity coefficients among species ranged from 0.66 to 0.97. The highest genetic similarity was observed between Dendrobium sp. Wanagiri and Dendrobium sp. Sepang, while D. fimbriatum was identified as the most genetically distinct species. These findings demonstrate a broad genetic base among Bali’s native Dendrobium species, indicating their strong potential as parental resources in hybrid breeding programs. The study also provides valuable molecular data that support the conservation and sustainable utilization of Bali’s native orchid germplasm for future cultivation and breeding initiatives.